Learning legal skills and reasoning - Hanson, Sharon; Kliem, Tobias; Waters, Benjamin D. (New York: Routledge, 2022)
'Language skills, study skills, argument skills and the skills associated with dispute resolution are vital to every law student, professional lawyer and academic. The fifth edition of Learning Legal Skills and Reasoning discusses the main sources of English law and explains how to work with legal texts in order to construct credible legal arguments which can be applied in coursework, exams or presentations. This book: Discusses how to find and understand sources of both domestic and European Union Law. Develops effective disciplined study techniques, including referencing, general reading, writing and oral skills and explains how to make good use of the university print and e-library. Contains chapters on writing law essays, problem questions and examinations, and on oral skills including presentations and mediation skills. Packed full of practical examples and diagrams across the range of legal skills from language and research skills to mooting and negotiation, this textbook will be invaluable to law students seeking to acquire a range of discrete legal skills in order to use them together to produce competent assessed work'--
Domestic legislation -- Domestic case law -- European and international law -- Human rights -- General study skills -- Finding material -- Reading and understanding domestic legislation -- Reading and understanding cases -- Constructing an argument -- Writing law essays (including referencing) -- Answering legal problem questions -- Oral presentations and mooting -- Examinations -- Negotiation skills -- Mediation skills -- Drafting skills.
Includes bibliographical references and index. (443-451 pages)
Puan Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 6393/ Pemilihan Ketua Perpustakaan Undang-Undang/ OC/ Bookline Services
Keywords: Law -- Great Britain -- Methodology; Law -- Great Britain -- Interpretation and construction; Law -- Great Britain -- Language